Bacterial pathogen spectrum of acute diarrheal outpatients in an urbanized rural district in Southwest China. (May 2018) - Zhou, Yongming; Zhang, Jingyun; Wang, Shukun; Xu, Wen; Liang, Weili; Yan, Meiying; Wang, Duochun; Diao, Baowei; Pang, Bo; Lu, Xin; Fan, Fenxia; Li, Jie; et al.
Highlights: The positive rate of common bacterial pathogens among the 797 samples was 24.8%. DEC had the highest detection rate, followed by Aeromonas, P. shigelloides, Salmonella . Molecular typing of strains suggested a possible outbreak once occurred. Abstract: Objectives: To conduct a one-year pathogen surveillance of acute diarrheal disease based on outpatient clinics in township hospitals in rural Hongta District of Yunnan Province, China. Methods: Fecal specimens of acute diarrhea cases and relevant epidemiological information were collected. Salmonella, Shigella, Vibrio, Aeromonas, Plesiomonas shigelloides and diarrheogenic Escherichia coli (DEC) were examined. Results: Among the 797 stool specimens sampled, 198 samples (24.8%) were positive in pathogen isolation, and 223 strains were isolated. The order of isolation rates from high to low were DEC, Aeromonas, P. shigelloides, Salmonella, Shigella and Vibrio . The overall positive rate in middle school students and preschool children was relatively high; while the overall positive rate of less than 1-year-old infants and above 55 years olds was relatively low. The isolates were analyzed by pulsed-field gel electrophoresis (PFGE). Some cases had the same or very close onset time, and the isolates had similar PFGE patterns, suggesting a possible outbreak once occurred but was not detected by the current infectious disease reporting system. Conclusions: Pathogen infection and transmission in rapidly urbanized rural areas is a serious issue. There is a great need for a more sensitive and accurate mode of monitoring, reporting and outbreak identification of diarrheal disease.